PARTISIPASI MASYARAKAT NELAYAN DALAM PENGEMBANGAN BUDAYA WISATA BAHARI DI KABUPATEN AGAM - Lucky Zamzami (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2015)
Tourism area development has always been associated with the empowerment of coastal communities. The coastal communities have a lot of knowledge about the objective region conditions, especially in the area tourism, always used approach to the local community as a model of participatory planning. Economic empowerment of coastal communities through the development of tourism area in Tiku coastal regions is integrated as an attempt ideal to address the issues of economic, social and ecological existing in coastal areas that not ignoring dimensions such as philosophy of empowerment, social-cultural potential of communities based on local wisdom local community